2007
DOI: 10.1007/s11257-007-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting time-sharing in mobile interaction

Abstract: The era of modern personal and ubiquitous computers is beset with the problem of fragmentation of the user's time between multiple tasks. Several adaptations have been envisioned that would support the performance of the user in the dynamically changing contexts in which interactions with mobile devices take place. This paper assesses the feasibility of sensor-based prediction of time-sharing, operationalized in terms of the number of glances, the duration of the longest glance, and the total and average durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Oulasvirta et al investigated how different environments affected attention while users waited for a web page to load on a mobile phone [32]. In a follow-up work, the same authors used a Wizard-of-Oz paradigm with simulated sensors to assess the feasibility of predicting time-sharing of attention, including prediction of the number of glances, the duration of the longest glance, and the total and average durations of the glances to the mobile phone [27].…”
Section: User Behaviour Modelling On Mobile Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oulasvirta et al investigated how different environments affected attention while users waited for a web page to load on a mobile phone [32]. In a follow-up work, the same authors used a Wizard-of-Oz paradigm with simulated sensors to assess the feasibility of predicting time-sharing of attention, including prediction of the number of glances, the duration of the longest glance, and the total and average durations of the glances to the mobile phone [27].…”
Section: User Behaviour Modelling On Mobile Devicesmentioning
confidence: 99%
“…Prior work mainly focused on estimating the point of gaze on the device screen using the integrated front-facing camera [15,52] or on using inertial sensors or application usage logs [7,10] to predict user engagement [26,47] or boredom [35]. In contrast, allocation of user attention across the device and environment has rarely been studied, and only using simulated sensors [27]. Most importantly, existing attentive user interfaces are only capable to adapt after the fact, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Maulsby et al (1993) used wizard-of-Oz to prototype an intelligent agent. Several recent UMUAI papers report on wizard-of-Oz studies (Miettinen and Oulasvirta 2007;Batliner et al 2008;Damiano et al 2008;Conati and MacLaren 2009). For example, Miettinen and Oulasvirta (2007) used wizard-of-Oz to simulate the system functionality that corresponds to the CID/ID layers: sensors were simulated by human codings of data.…”
Section: User Testsmentioning
confidence: 99%
“…Several recent UMUAI papers report on wizard-of-Oz studies (Miettinen and Oulasvirta 2007;Batliner et al 2008;Damiano et al 2008;Conati and MacLaren 2009). For example, Miettinen and Oulasvirta (2007) used wizard-of-Oz to simulate the system functionality that corresponds to the CID/ID layers: sensors were simulated by human codings of data. In a layered evaluation, wizard-of-Oz can also be useful to simulate layers preceding the one being evaluated, to ensure these work perfectly and to enable the evaluation of a layer in isolation.…”
Section: User Testsmentioning
confidence: 99%
“…The side effects of this competition on the user's performance are termed as cognitive resource depletion (CRD) in the area of cognitive psychology [63]. This leads to distractions; increases errors, stress, and frustration; and reduces the ability to perform mental planning, problem solving, and decision making [20,42,45]. In particular, recent studies have shown how annoying technostress is to users [38,39,48].…”
Section: Introductionmentioning
confidence: 99%